Calculating the Soil Freezing Characteristic Curve of Saline Soil With Equivalent State of Bulk Solution - Lihong Cui; Zean Xiao; Junfeng Chen; Qinbo Yuan; Xuehua Zhao; Jing Xue (Water Resources Research)
Abstract The relationship between unfrozen water content and temperature, called as soil freezing characteristic curve (SFCC), is of importance for hydrologic, engineering, environmental issues related to frozen soil. The SFCC of saline soil is essentially a result of phase equilibrium of pore solution, which is similar but not identical to that of bulk solution. However, there is still a vacancy of study on the phase equilibrium of pore solution in frozen soil. In this study, image transformation was used to establish the relationship of phase equilibrium between bulk solution and pore solution, with four introduced parameters. Then, the new model of SFCC for saline soil was proposed based on the equivalent state of bulk solution with Pitzer model and SFCC of nonsaline soil. The model was validated by the experimental data from published articles and showed good performance in calculating SFCC of saline soils regardless of soil type, phase transition path, and soil initial water‐salt condition, and some advantages when compared to other three models. All the four introduced parameters have clear physical meanings and their relationships with soil type and initial salt concentration were discussed. Finally, the evolution of phase diagram from bulk solution to pore solution at icing stage was figured out. Further studies are needed for their relationship at salt crystallization stage. Shifting the research perspective from unfrozen water content to pore solution, this study gives a new approach to research of freezing characteristic of saline soil and could promote hydrological and engineering research in cold regions.